Enterohemorrhagic E. coli effector NleL disrupts host NF-κB signaling by targeting multiple host proteins. (17th February 2020) - Sheng, Xiangpeng; You, Qing; Zhu, Hongnian; Li, Qingrun; Gao, Hong; Wang, Haifeng; You, Chunping; Meng, Qing; Nie, Yingjie; Zhang, Xiangyan; Hu, Ronggui
Graphical Abstract: